MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI PENGURANGAN BILANGAN DALAM BENTUK SOAL CERITA - Irma Sari Daulay (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
The problem in this study was motivated by the low ability of students in number reduction material in the form of word problems in class IV SD Negeri 1001 Batang Bulu. The low ability of students is seen from the learning outcomes that have been achieved which do not meet the standards set. If this problem is not immediately sought to have an impact on further learning material, it will produce a gap between learning outcomes and the results achieved. Therefore, a solution is needed to overcome these problems, by applying a problem-based learning model that is believed to be able to solve the problem well. The method used in the research was classroom action research with 23 fourth grade students at SD Negeri 1001 Batang Bulu as subjects. The planned stages are two cycles with limitations on student success according to established standards. The research instrument used consisted of tests and observations. The findings obtained in this study showed a marked increase in the average results in cycle II of 95.65%. That is, the problem-based learning model can improve student learning outcomes in the matter of reducing numbers in the form of word problems in class IV SD Negeri 1001 Batang Bulu.